Exploring the Factors explaining Length of Stay at Emergency Department: Study in a C Class Private Hospital - Amalia, Eta Riska (Fakultas Kedokteran Universitas Brawijaya)
ABSTRACTThe process of admitting patients to the inpatient wardfrom the emergency room is of the factors that influence the access block time in services in the emergency room and hospitals. This study aimed to identify the cause of transition time to inpatient services from the emergency room at a private C class hospital in Malang. This research is a descriptive exploratory study using interviews withfour general practitioners, two emergency nurses, two general inpatient nurses, two children inpatient nurses, and one administrative staff, and also observation of the stages and duration of emergency services and inpatient care. The process from arrival, registration, and inspection takes 0-15 minutes. Overall, the stages of registration until the inpatient ward transfer require 1-3.5 hours, which exceeds the hospital quality standards. Factors that influence the transfer time are the condition of the patient, the absence of a transition room, the availability of inpatient wards, and the patient discharge process. To manage ER LOS, especially block access to inpatient services, hospitals need to apply Bed Management properly.Â Â